Long-term evolutionary persistence of a cryptic color polymorphism in frogs - Sandra Goutte; Stéphane Boissinot (Proceedings of the National Academy of Sciences, 2025)
Color polymorphism can influence the evolutionary fate of cryptic species because it increases populations’ chances of survival in heterogenous or variable environments. Yet, little is known about the molecular and evolutionary mechanisms underlying the persistence of cryptic color polymorphisms, or the impact these polymorphisms have on the macroevolutionary dynamics of lineages. Here, we examine the evolutionary history of the most widespread cryptic color polymorphism in anurans, involving green and brown morphs. Using an order-scale comparative analysis, we show that these morphs can coexist within species over long evolutionary periods and that polymorphic lineages switch habitat more frequently and have greater diversification rates than other groups. We then identify the locus responsible for the green/brown polymorphism in a group of African grass frogs, and demonstrate that it evolves under long-term balancing selection, resulting in trans-specific polymorphism. These results provide a microevolutionary mechanism for the long-term persistence of multiple color morphs within species observed at a macroevolutionary scale. This study underscores the importance of cryptic color polymorphism in the ecology and evolution of anurans, and provides a framework for future research on the genetic architecture and selective forces underlying cryptic coloration traits.